Das Odeion im Artemision von Ephesos - Zabrana, Lilli (Verlag der Österreichischen Akademie der Wissenschaften, 2019)
In the 125 years of research, the legendary temple of Artemis was always the focus of the archaeological fieldwork, while the once densely built up sacred enclosure remained unexplored. Since 2009 the Austrian Archaeological Institute investigated for the first time a roman building southwest of the Temple, which was up to the present named 'Tribune' and whose function could be finally clarified. Due to close typological parallels as well as equipment and furnishing, the building can be identified as roman Odeion of the Early Empire.